Defected Ground Structure Microstrip Patch Antenna Design for Radio Frequency identification (RFID) and Wireless Communications - Aslam, Muhammad Azeem; Maryam, Hina (Journal of Cross-Disciplinary Sustainability Innovations, 2025)
The future of wireless communications such as WLAN (IEEE 802.11ah), radio frequency identification (RFID), wireless sensor networks, structure health monitoring, and home automation will integrate defected ground structure (DGS) antennas. The proposed design having defected ground structure (DGS) antenna design suited for RFID and wireless system operation. Working at 1.96 GHz, this DGS antenna has an exceptional return loss of -31 dB against antenna I which is having frequency of 1.93 GHz and a return loss of -13 dB. The SAR analysis factor proves its appropriateness for human-friendly. This study supports the feasibility of the antenna for improving the performance and ability of the system with the functioning of the ultra-high frequency (UHF) frequency range with the help of simulation and fabrication.